Analisis Penerapan Model Blended Learning Dalam Kurikulum Merdeka Belajar Pada Mata Pelajaran PAI di SMA N 2 IV Koto Kabupaten Agam - Oktarina, Ulfa; Yusra, Oktarina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The analysis of the application of the blended learning model in the independent learning curriculum in Islamic religious education subjects did not run optimally due to limited time, in addition to the obstacles experienced such as cellphones that often died and also many different students and of course in Islamic Religious Education lessons for instilling religious values it was difficult to see and control because of limited communication, teachers cannot directly reprimand, or advise students when they make mistakes. This can make students passive and less attentive to learning. The type of research used is field research, the data collection techniques are in the form of observation, interviews, and documentation. Then the data validity technique is in the form of researcher participation and triangulation, data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. The informants in this study were the vice principal, Islamic Religious Education teachers, and students of SMA N 2 IV KOTO, Agam Regency. The results of the study showed that the analysis of the application of the blended learning model in the independent learning curriculum in Islamic Religious Education subjects consisted of three stages, namely the planning stage consisting of two sessions, preparing materials, and preparing learning media. The implementation stage includes preliminary activities in the form of opening learning, reciting the Koran, the core of delivering the material, and the evaluation or assessment stage in the form of assignments given and practical videos. In addition, there are supporting factors and inhibiting factors in the analysis of the application of the blended learning model in the independent learning curriculum. The supporting factors include 1) Ease of access to technology, 2) Easy access to learning resources, 3) Support from the family environment. While the inhibiting factors include 1) Unstable signal network, 2) Low student learning motivation, and 3) Limited learning facilities.